Acceptance and Commitment Therapy Effectivity towards Parents Stress – Meta Analysis - Kezia Jeni Hindrawan; Ananta Yudiarso (Green Publisher, 2025)
Background: Stress in parents inhibits their abilities to optimize parenting role. Acceptance and Commitment Therapy (ACT) helps parents to embrace their feelings and thoughts to be more committed in achieving well-being. Objective: This study aims to analyze the effectiveness of ACT to reduce stress in parents. Method: This research use meta-analytical method from RCT studies to provide in-depth analysis. Results: Result shows a large effect of ACT toward stress intervention within parents particularly in group-based format (I2 = 93.01%). Conclusion: This research has given significance proof to use ACT in order to reduce stress within parenting context. Further research should be focused on ACT intervention in Asian parents context with RCT, especially Indonesia.